Tuberculosis in pregnancy and adverse neonatal outcomes in two peruvian hospitals - Garay-Aguilar, Noelia V. (2024)
Background: According to the World Health Organization, tuberculosis (TB) ranks among the top 10 causes of death worldwide. The significance of TB during pregnancy lies in its symptoms, which can be mistaken for physiological changes associated with pregnancy. This confusion can lead to maternal-perinatal complications. Objective: To evaluate the association between pulmonary TB in pregnancy and adverse neonatal outcomes in two Peruvian hospitals. Methods: This is a retrospective cohort study. The target population consisted of pregnant women with and without pulmonary TB whose deliveries were attended at two public hospitals, located in Lima, Peru. The adverse neonatal outcomes were prematurity, low birth weight (LBW), and being small for gestational age (SGA). Crude and adjusted relative risks (RRa) were calculated with their respective 95% confidence intervals (95%CI). Results: Information from 212 patients was analyzed; 48.1% had TB during pregnancy, and 23.1% had adverse neonatal outcomes (8%, 11.3%, and 12.3% for LBW, prematurity, and SGA, respectively). In the adjusted model, pregnant women with pulmonary TB had a 3.52 times higher risk of having a newborn with at least one of the adverse outcomes than those who were not exposed (aRR, 3.52; 95%CI: 1.93–6.68). Conclusion: Pulmonary TB in pregnancy was jointly and independently associated with adverse neonatal outcomes, including LBW, prematurity, and being SGA.